60, 000 Years is not forever: 'time revolutions' and Indigenous pasts. Issue 4 (2nd October 2022) - Rademaker, Laura
ABSTRACT: Settler Australia is sometimes said to have experienced a 'time revolution' on realizing that Aboriginal people have dwelt here for millennia, mirroring the earlier European 'time revolution' when Europeans discovered humanity's 'deep' past. This essay unpicks these twin 'revolutions' and explores how the idea of 'time revolutions' serves a settler society such as Australia. I suggest that celebration of quantitative 'revolutions' obscures qualitative shifts in European times and sidelines Indigenous way-of-being in time. I wonder about the possibility of a more fundamental 'time revolution', that is, a turning to see that time might not be simply linear, universal and homogenous.